PERADABAN MASA SEJARAH SITUS EREKE, BUTON UTARA, SULAWESI TENGGARA [1] (The Historical Civilization of Ereke Site, North Buton, Southeast Sulawesi) - Mahmud, M. Irfan (BALAI ARKEOLOGI PAPUA, 2014)
Ereke is one of regions in the north of Buton Island which grew in the authorization of Muna Palace.Under the threat of pirates and the greatness of Waolio Castle (Buton) and Muna, they built their government in a fortress (intra-murros). It was divided into some units with “kalisusu” as physical symbol of residential centre, and it became their identity. This paper will reveal the archaeological trackin historical landscape. To describe some aspects of community civilization in the history of Ereke archaeological site. At least since XV until XIX centuries. The purpose is to give initial information which can be developed in the broader and deeper research in the future. There was one significant thing found using archaeological survey, although cultural acculturation and assimilation occurred transparently, but the substantive element of local culture can hold up as the identity by adapting the external influence, such as defence system, fortress, armament, import goods, and religious order of the society. ABSTRAKEreke merupakan kawasan di sisi utara pulau Buton yang tumbuh dalam pengaruh penguasa keraton Muna. Di bawah ancaman bajak laut dan bayang-bayang kebesaran keraton Wolio (Buton) dan Muna, mereka membangun pemerintahan dalam benteng (intra-murros). Ruang benteng terbagi dalam beberapa unit, dengan “Kalisusu” sebagai simbol pusat permukiman, sekaligus menjadi identitas yang merekatkan. Tulisan ini akan mengungkapkan jejak arkeologis dalam bentang sejarah (historical landscape) untuk menggambarkan beberapa aspek peradaban komunitas di situs Ereke masa sejarah, sekurang-kurangnya sejak abad XV hingga XIX. Tujuannya, untuk memberikan informasi awal yang dapat dikembangkan dalam penelitian yang lebih luas dan mendalam di masa akan datang. Ada satu hal yang penting ditemukan dengan survei arkeologis, bahwa meskipun akulturasi dan assimilasi budaya berlangsung terbuka, namun unsur subtantif budaya lokal mampu bertahan sebagai identitas dengan tetap mengadaptasi anasir luar, seperti sistem pertahanan (benteng), persenjataan, barang impor, dan tatanan keagamaan.